An unusual band causing intestinal obstruction: case report - Chelliah, Suresh; Jayabalan, Sathia Dev; Pachamuthu, Meganathan; Veettil, Nimisha Puthiya (International Journal of Contemporary Pediatrics, 2020)
We report an unusual case of intestinal obstruction. The child presented with intermittent abdominal pain. Initial USG abdomen and CT abdomen were inconclusive. Diagnostic laparoscopy followed by Laparotomy was done to remove bezoar made up of a rubber band and thread balls. Iron and zinc deficiencies are the preventable causes of pica. Plasticobezoars are rare and should be suspected when symptoms are not consistent with other common causes of obstruction.